2020
DOI: 10.1155/2020/8109858
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Treatment Outcome and Its Predictors among Ambulatory Patients with Epilepsy at Mizan-Tepi University Teaching Hospital, Southwest Ethiopia

Abstract: Background. Epilepsy is among the most common neurological disorders which is highly treatable with currently available antiepileptic drugs at a reasonable price. In Ethiopia, despite a number of studies revealed high prevalence of epilepsy, little is known on predictors of poorly controlled seizures. us, the aim of this study was to assess epilepsy treatment outcome and its predictors among patients with epilepsy on follow-up at the ambulatory care unit of Mizan-Tepi University Teaching Hospital, Southwest Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(56 citation statements)
references
References 29 publications
9
45
2
Order By: Relevance
“…This may be explained in part by the fact that patients with higher 7 Behavioural Neurology seizure frequency can have a risk of head injury due to convulsion that triggers seizure [17]. It is ascertained that medication nonadherence was responsible for uncontrolled seizure [29,30,37]. The result of this meta-analysis also confirmed this conclusion by revealing that nonadherent participants were 2.23 times more likely to have uncontrolled Behavioural Neurology seizure compared to participants which adhered to their medication.…”
Section: Behavioural Neurologysupporting
confidence: 57%
See 2 more Smart Citations
“…This may be explained in part by the fact that patients with higher 7 Behavioural Neurology seizure frequency can have a risk of head injury due to convulsion that triggers seizure [17]. It is ascertained that medication nonadherence was responsible for uncontrolled seizure [29,30,37]. The result of this meta-analysis also confirmed this conclusion by revealing that nonadherent participants were 2.23 times more likely to have uncontrolled Behavioural Neurology seizure compared to participants which adhered to their medication.…”
Section: Behavioural Neurologysupporting
confidence: 57%
“…Twentythree primary studies were included in the present systematic review and meta-analysis. These studies were conducted in different parts of Ethiopia (from Amhara seven primary articles [7,[13][14][15][16][17][18], Oromiya eight [8,9,[19][20][21][22][23][24], Addis Ababa four [25][26][27][28], Tigray two [9,29], and Southern Nation, Nationalities, and People two articles) [30,31]. The sample size of the included primary studies was considerably variable ranging from 121 to 415 participants.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 40 Two-thirds of patients with controlled seizure achieved seizure control with single ASM use, which was congruent with reports from other sub-Saharan African countries. 16 18 , 21 23 Several Western studies have shown that the response to the first ASM is the best predictor of long-term outcome. Seizures that continued despite adequate doses of an appropriate had a lower chance of subsequent seizure remission.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Despite significant therapeutic advances in the control of epileptic seizures, in 20–30% of patients, epileptic seizures are not well controlled, and patients who are controlled with medication(s) are not free from unwanted adverse effects and its various problems. 2 The symptoms of epilepsy fall in a wide range, of which some people with absence epilepsy stare for a few seconds during a seizure, while others with generalized epilepsies may experience tonic-clonic seizures. 3 Epilepsy is diagnosed based on history, physical examination, and paraclinical tests, in particular, electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%